STUDENTS’ OPINIONS REGARDING STRATEGIC MANAGEMENT COURSE’S INSTRUCTED IN THE GRADUATE PROGRAMS LEVEL OF GAINING QUALIFIED EMPLOYEE TO BUSINESS: A STUDY AT GAZI UNIVERSITY - Öztürk, Zekai; Kızılkaya, Selman; Çağatay, Altuğ (International Online Journal of Education and Teaching, 2016)
At the point of monitoring developments taking place in the internal and external environmental conditions of the businesses, gaining the necessary skills is critical. To gain these skills, conscious and visionary individuals are given strategic management course in the universities at the associate degree, undergraduate, graduate and doctor’s degree. In this study, students’ opinions regarding the level of strategic management course’s gaining to business with qualified employee were given. To serve this purpose, a research was made on students in Gazi University Social Sciences Institute, registered in 2015-2016 fall semester master’s and doctoral level and taking a strategic management course. Independent Sample T-Test using for comparison and a parametric method analysis was applied to data obtained. As a result of the study, it is observed that students educated in master’s and doctoral level expressed their opinions concerning the strategic management course as an important tool to function in providing qualified employee to business in the middle level. As a result of analysis, it is observed that gaining qualified employee to business in a strategic management course is the level of 3, 32 in graduate students and 2, 63 in doctoral students.